PROGRAM LATIHAN BAGI KELOMPOK LANSIA - Afriwardi Afriwardi (Jurnal Kesehatan Masyarakat Andalas, 2008)
The increase of older people can be seen in our health service .Some of the older people is living in a bad condition where they need helpfrom their children or family. The study to stay young is most interest to reduce the aging of human body that coz malfunction of human body. Training to the older people need to be given to slower down their aging and degenerative disease. The planning ofthese program is good for the older people to get the optimal effect. The training program should be to the role of exercise that is good, well, arrange, andprogressive.